2019
DOI: 10.1136/bmjopen-2018-025066
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and determinants of postnatal care use in Ethiopia: findings from the 2016 demographic and health survey

Abstract: ObjectivePostnatal care (PNC) is essential for preventing maternal and newborn deaths; however, it still remains less well recognised in low-income and middle-income countries. This study was aimed to explore geographical patterns and identify the determinants of PNC usage among women aged 15–49 years in Ethiopia.MethodsA secondary data analysis was conducted using the 2016 Ethiopian demographic and health survey data. A total of 7193 women were included in this analysis. We employed spatial scan statistics to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 21 publications
14
49
1
1
Order By: Relevance
“…(63%) (25). Though, this finding was higher than the 2016 DHS report 6.9% in Ethiopia [ 16 ], 2013 DHS 29% in Nigeria [ 18 ], 2015/2016 DHS 48.4% in Malawi [ 17 ], and a systematic review conducted in developing countries (36%) [ 12 ]. The possible reason for the observed difference might be occurred due to the existence of health system infrastructure and socio-cultural variations across countries.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…(63%) (25). Though, this finding was higher than the 2016 DHS report 6.9% in Ethiopia [ 16 ], 2013 DHS 29% in Nigeria [ 18 ], 2015/2016 DHS 48.4% in Malawi [ 17 ], and a systematic review conducted in developing countries (36%) [ 12 ]. The possible reason for the observed difference might be occurred due to the existence of health system infrastructure and socio-cultural variations across countries.…”
Section: Discussionmentioning
confidence: 78%
“…In the previous studies, the logistic regression model was used, which cannot address a problem of nonindependence [1,3,13,16,17]. But in this study, we used the multilevel model, which can handle both individual and community-level characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, region was another important factor that was associated with delayed PNC attendance in which women from Oromia and Gambela region had higher odds of delayed first PNC attendance. Other studies also revealed region as an important factor for the utilization of maternal health services including postnatal care [ 24 , 37 , 38 ]. The possible explanation for this might be due to the sociocultural difference between regions as well as the differences in the accessibility and quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…According to Koblinsky and colleagues [ 13 ], the traditional home confinement of women after childbirth in Ethiopia contributes to the low use of PNC services. Others also reported significant regional variations in the use of ANC in Ethiopia with low levels reported in Somali, Oromia, Gambella and Southern Nations, Nationalities, and People’s Region (SNNPR) [ 14 ]. These findings imply the need for national and regional level interventions that target individual women, their families and surrounding communities as well as health care professionals and the wider health care system to improve the utilisation of maternity care services in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%